2017
DOI: 10.3390/nu9121297
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sialyllactose Influences Sialic Acid Concentrations in the Prefrontal Cortex and Magnetic Resonance Imaging Measures in Corpus Callosum of Young Pigs

Abstract: Sialic acid (SA) is a key component of gangliosides and neural cell adhesion molecules important during neurodevelopment. Human milk contains SA in the form of sialyllactose (SL) an abundant oligosaccharide. To better understand the potential role of dietary SL on neurodevelopment, the effects of varying doses of dietary SL on brain SA content and neuroimaging markers of development were assessed in a newborn piglet model. Thirty-eight male pigs were provided one of four experimental diets from 2 to 32 days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 29 publications
(50 reference statements)
0
61
2
Order By: Relevance
“…Neu5Ac brain concentration, expression of two learning associated genes and learning and memory abilities were positively impacted by the Sia supplementation. However, a research team has recently reported two studies in which supplementation with sialyllactose from PN2–PN22 or PN32 in piglets showed no significant effect on recognition memory [ 50 ], but did show a sialic acid increase in hippocampus, prefrontal cortex and corpus callosum [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neu5Ac brain concentration, expression of two learning associated genes and learning and memory abilities were positively impacted by the Sia supplementation. However, a research team has recently reported two studies in which supplementation with sialyllactose from PN2–PN22 or PN32 in piglets showed no significant effect on recognition memory [ 50 ], but did show a sialic acid increase in hippocampus, prefrontal cortex and corpus callosum [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jacobi et al also demonstrated in piglets that a formula supplemented with dietary 6′-SL and 3′-SL increased the sialic acid bound to gangliosides in several areas of the brain [ 52 ]. As described above, Mudd and co-workers have recently published a study in which piglets were fed several diets containing different doses of sialyllactose from PN2–PN32 and showed that dietary sialyllactose increased conjugated Neu5Ac in the prefrontal cortex, among other brain structures [ 51 ]. In our study, Neu5Ac determination by HPLC was done in the whole hemisphere instead of in separate structures.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated supplemental sialylated HMO using whey fractions from bovine milk that are enriched with 3 -SL and 6 -SL, but also contain lactose and other whey components [12]. Having pure forms of 3 -SL and 6 -SL would enable precise supplementation of these HMOs in terms of concentrations and ratios.…”
Section: Introductionmentioning
confidence: 99%
“…HMOs function as the first prebiotics for infants, but are also suggested to support infant health, growth, and development by acting as antimicrobials, antiadhesives, and modulators of cell responses [ 14 , 15 , 16 ]. Several beneficial effects of sialylated HMOs related to intestinal function, microbial colonization and immunity in newborns have been documented in vitro and in pre-clinical animal models [ 17 , 18 , 19 , 20 ]; for example, the content of disialyllacto-N-tetraose in the milk has been identified as a potential marker of preterm infants at risk of developing necrotizing enterocolitis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 3’SL and 6’SL have been also shown to reduce anxiety-related parameters in juvenile mice [ 18 ]. Here, SL supplementation increased the free-to-bound hippocampal sialic acid, reduced bound sialic acid in the prefrontal cortex, and increased mean, axial and radial diffusivity in the corpus callosum in newborn term pigs in a dose-dependent manner, with positive effects at an intermediate dose of 380 mg SL/L milk replacer [ 19 ]. While these studies strongly suggest brain developmental effects of dietary SL, the gut-brain mechanisms of these maturational effects remain unknown.…”
Section: Introductionmentioning
confidence: 99%